Anxiety levels related to surgery and pain intensity in patients scheduled for lumbar surgery - ÜNAL, Ayşe; CİVLAN, Serkan and YAĞCI, Nesrin and ALTUĞ, Filiz (Göbeklitepe Medical Science Journal, 2022)
This study aimed to determine the relationship between pain intensity and anxiety levels related to surgery in patients scheduled for lumbar surgery due to low back pain. Fifty-seven patients (30 females, 27 males) scheduled for lumbar surgery for various reasons were included in the study. Demographic and clinical information of the patients were recorded. The state of being informed about the surgery and the reasons for anxiety about the surgery were questioned. Pain intensity at rest, in activity, and at night were evaluated using the Visual Analogue Scale and surgery-related anxiety levels with the Spielberg State-Trait Anxiety Inventory preoperatively, postoperatively, and at discharge. Mean age of the patients was 55.00±9.37 years. A statistically significant positive correlation was found between the intensity of rest, activity, night pain, and the anxiety level in the preoperative period (p<0.05). Patients who were informed about surgery had lower anxiety levels (p<0.05). In the postoperative and pre-discharge evaluations, it was observed that there was a significant decrease in pain intensity and anxiety levels compared to the preoperative term (p<0.05). When evaluating the patient in the preoperative period, assessment of the level of anxiety related to surgery and informing about the surgical intervention will decrease the anxiety level and positively affect the postoperative clinical situation.